Evidence for in-plane tetragonal c-axis in MnxGa1–x thin films using transmission electron microscopy. (15th March 2016) - Karel, J.; Casoli, F.; Lupo, P.; Nasi, L.; Fabbrici, S.; Righi, L.; Albertini, F.; Felser, C.
Abstract: Tetragonal Mnx Ga1–x ( x = 0.70, 0.75) thin films grown on SrTiO3 substrates exhibit perpendicular magnetic anisotropy with coercive fields between 1 and 2 T. Transmission electron microscopy (TEM) and X-ray diffraction (XRD) reveal that 40 nm samples grown at 300–350 °C lead to films with the tetragonal c-axis oriented primarily perpendicular to the film plane but with some fraction of the sample exhibiting the c-axis in the film plane. This structure results in an undesirable secondary magnetic component in the out of plane magnetization. Growth at 300 °C with a reduced thickness or Mn concentration significantly decreases the tetragonal c-axis in the film plane. Graphical abstract: